Psychometric properties of the Propensity to Morally Disengage Scale in Peruvian university students: internal structure and association with the dark triad - Lingán-Huamán, Susana K.; Dominguez-Lara, Sergio; Serpa-Barrientos, Antonio (Frontiers in Education, 2023)
Introduction Human morality is an important topic because the fact that human beings can determine if a behavior is correct or incorrect, good or bad, shows that they are endowed with moral conscience, but In the Peruvian context, there are no valid and reliable scales to measure moral disengage trend. This study aimed to analyze the psychometric properties of the Propensity to Morally Disengage Scale in Peruvian university students. Method The number of university students who participated in the study was 591 (women = 71.7%; Mage = 21.5; SDage = 3.60), and the data analysis was carried out under a factor analysis approach. Results The results showed a unidimensional structure in both men and women. As for the invariance results according to sex, there is favorable evidence of configural and weak invariance; however, there is no evidence of strong invariance. Furthermore, the reliability of the construct (coefficient ω) and its scores (coefficient α) reached acceptable dimensions in each group and positive associations with the dark triad (Machiavellianism, psychopathy, and narcissism). Discussion The Propensity to Morally Disengage Scale is a unidimensional measurement that shows acceptable psychometric evidence in men and women separately. The theoretical and practical implications are discussed.